2016
DOI: 10.3109/07420528.2015.1121876
|View full text |Cite
|
Sign up to set email alerts
|

Working “out-of-phase” with reference to chronotype compromises sleep quality in police officers

Abstract: The aim of this work was to study the sleep characteristics, blood pressure (BP) and heart rate (HR) of the police officers working during out-of-phase (OP) and in-phase (IP) duty schedules with respect to their chronotypes. Adult male and female police officers (n = 85) were asked to answer Hindi/English version of different questionnaires to assess their chronotype (morningness-eveningness questionnaire; MEQ), PSQI scores (Pittsburgh sleep quality index), daytime sleepiness (Epworth sleepiness scale, ESS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Further support in the relationship of matching chronotype to shift timing was found in the studies focused on sleep characteristics 20 , 45 , 47 , 48 , 49 ) . The research strongly supported chronotype misaligned with shift timing was associated with decreased sleep duration and quality 20 , 48 ) . In fact, Juda et al ’s 20 ) data analysis supported ET workers matched with evening shift reported longer sleep duration than MT workers on the same shift.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Further support in the relationship of matching chronotype to shift timing was found in the studies focused on sleep characteristics 20 , 45 , 47 , 48 , 49 ) . The research strongly supported chronotype misaligned with shift timing was associated with decreased sleep duration and quality 20 , 48 ) . In fact, Juda et al ’s 20 ) data analysis supported ET workers matched with evening shift reported longer sleep duration than MT workers on the same shift.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, older workers reported decreased sleep duration and quality, regardless of shift timing. In studying police officers in India, Yadav et al 48 ) found participants had decreased sleep duration and quality when working shifts misaligned with their identified chronotype.…”
Section: Resultsmentioning
confidence: 99%
“…Police officers who were poor sleepers experienced significant improvements in their sleep quality when they were allowed to work "in phase" with their chronotype (i.e. morning or evening shifts) (Yadav et al 2016). This indicates that a discrepancy between an individual's chronotype and social obligations, which is more likely to occur in evening types, is related to poor sleep quality (Yadav et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…morning or evening shifts) (Yadav et al 2016). This indicates that a discrepancy between an individual's chronotype and social obligations, which is more likely to occur in evening types, is related to poor sleep quality (Yadav et al 2016). Subsequently, insufficient sleep leads to worsened mood and decreased ability to regulate negative emotions (Baum et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This scale has the sensitivity of approximately 90% and specificity around 87% to differentiate between good sleepers and poor sleepers. This questionnaire has been used in both original and Hindi version in India [18][19][20][21]. English version of this questionnaire has been validated against polysomnography [21].…”
Section: Measurement Of Sleep Qualitymentioning
confidence: 99%